HETERONORMATIVITAS DAN PERKEMBANGAN IDENTITAS SEKSUAL ANAK REMAJA - Massuhartono, Massuhartono (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
This study aims to understand how heteronormativity affects the development of adolescent sexual identity through the school, family, and social media environment. Using a qualitative approach with in-depth interview methods, participatory observation, and documentation analysis, this study explores adolescents' experiences in navigating their sexual identities amid heteronormative social pressures. The results of the study showed that dominant heteronormative norms in schools, conservative attitudes in families, and limited social media representation can cause psychological and emotional distress in adolescents. Support from peers, inclusive teachers, and an accepting online community is an important resource for teens to overcome these challenges. This research emphasizes the importance of creating a more inclusive and supportive environment for adolescents to express their sexual identity authentically. The implications of these findings highlight the need for more inclusive education programs and increased awareness of the diversity of sexual identities among families and communities.